2007
DOI: 10.1002/eji.200636553
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of dendritic cell function by excretory‐secretory products: A potential mechanism for nematode‐induced immunosuppression

Abstract: To determine whether helminth-derived products modulate dendritic cell (DC) function, we investigated the effects of excretory-secretory products (ES) and adult worm homogenate (AWH) derived from the gastrointestinal nematode Heligmosomoides polygyrus (Hp) on murine bone marrow-derived DC (BMDC). Compared to the TLR9 ligand CpG, Hp-derived products alone failed to induce DC activation. ES, but not AWH, inhibited BMDC cytokine and chemokine production and co-stimulatory molecule expression (CD40, CD86 and MHC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
159
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(165 citation statements)
references
References 70 publications
4
159
2
Order By: Relevance
“…DCs typically acquire regulatory properties in the presence of TGF-b (47). Although the effect of HES in our in vitro cocultures was mainly on the T cells, H. polygyrus and the excretory-secretory products are also know to facilitate regulatory and Th2-promoting DC (31,(48)(49)(50). Interestingly, we found that preconditioning the site of BCG infection with TGF-b or HES significantly reduced BCGtriggered migration of DC (MHC-II hi CD11c +/int cells) to the draining LN.…”
Section: Discussionmentioning
confidence: 68%
“…DCs typically acquire regulatory properties in the presence of TGF-b (47). Although the effect of HES in our in vitro cocultures was mainly on the T cells, H. polygyrus and the excretory-secretory products are also know to facilitate regulatory and Th2-promoting DC (31,(48)(49)(50). Interestingly, we found that preconditioning the site of BCG infection with TGF-b or HES significantly reduced BCGtriggered migration of DC (MHC-II hi CD11c +/int cells) to the draining LN.…”
Section: Discussionmentioning
confidence: 68%
“…Heligmosomoides polygyrus excretory-secretory products (HES) modulate the host immune response and suppress Th2-mediated inflammation by a number of mechanisms (outlined in Figure 7), including: a) Inhibition of dendritic cell responsiveness to stimulation 25 , b) induction of CD4 +…”
Section: Discussionmentioning
confidence: 99%
“…A feature shared by many helminths is their capacity to suppress TLR-mediated DC activation by microbial PAMP. Numerous studies have reported the inhibitory effects of helminth-derived components on TLR-induced activation as determined by pro-inflammatory cytokine production and expression of MHC class II/costimulatory molecules [28,[33][34][35][36][37][38][39]. The pathways underlying this suppression are, however, still poorly understood.…”
Section: Modulation Of DC Function By Direct Interaction With Helmintmentioning
confidence: 99%
“…Yet, little is known about the role of DC during helminth infections in this phenomenon and the underlying molecular mechanisms. The few reports that have identified helminth-derived components that directly act on DC to drive IL-10-producing adaptive Treg (Tr1 cells) [12,34] did not address the molecular mechanisms by which DC prime regulatory responses. Apart from helminthderived products, host-derived cytokines such as IL-10 and TGF-b, or apoptotic cells generated during helminth infections are likely to play an important role in DC-driven Treg induction.…”
Section: Mechanisms Behind Dc-driven Treg Inductionmentioning
confidence: 99%